Bioindicators of heavy metal contamination in soil and vegetation around abandoned mining sites: Implications for ecological restoration - Abbas, Zainab M.; Shandookh, Fatima Kareem (Brawijaya University, 2026)
Derelict mines are chronic sources of heavy metals, threatening ecosystem integrity and human health. This study evaluated native flora and soil composition as bioindicators of contamination in three abandoned mining areas in Wasit Province, Iraq: Al-Aziziyah (lead-zinc), Old Kut (copper-cobalt), and Northern Al-Numaniyah. Soil and vegetation samples were analyzed via Atomic Absorption Spectrophotometry (AAS) for Pb, Cd, As, Cr, Zn, and Cu. Findings revealed Al-Aziziyah soils exceeded Iraqi/WHO limits for Pb (1,842 mg/kg; 36×) and Cd (12.7 mg/kg; 25×). The Geoaccumulation Index (Igeo) categorized Pb and Cd as